Ultrasmall FeS2 Nanoparticles‐Decorated Carbon Spheres with Laser‐Mediated Ferrous Ion Release for Antibacterial Therapy. Issue 13 (4th March 2021) - Xi, Juqun; An, Lanfang; Huang, Yaling; Jiang, Jian; Wang, Yanqiu; Wei, Gen; Xu, Zhilong; Fan, Lei; Gao, Lizeng
Abstract: Recent progress in nanotechnology and the ancient use of sulfur in treating dermatological disorders have promoted the development of nano‐sulfides for antimicrobial applications. However, the variable valences and abundant forms of nano‐sulfides have complicated investigations on their antibacterial activity. Here, carbon nanospheres (CNSs) with decoration of ultrasmall FeS2 nanoparticles (CNSs@FeS2 ) is synthesized, and their antibacterial ability and mechanism are explored. The CNSs@FeS2 released Fe 2+ and sulfur ions simultaneously through dissolution and disproportionation. In vitro study indicated that the released Fe 2+ killed bacteria by increasing the oxidative state of bacterial surfaces and intracellular molecules. Importantly, the released sulfur exhibited a protective effect on Fe 2+, ensuring the stable existence of Fe 2+ to continuously combat bacteria. Moreover, the carbon shells of CNSs@FeS2 not only prevented the aggregation of FeS2 but also accelerated the release of Fe 2+ through photothermal effects to achieve synergistic hyperthermia/Fe 2+ therapy. In vivo experiments indicated that treatment with CNSs@FeS2 resulted in a marked reduction in bacterial number and improvement in survival in an acute peritonitis mouse model, and antibacterial wound experiments demonstrated high efficacy of CNSs@FeS2 ‐enabled synergistic hyperthermia/Fe 2+ therapy. Thus, this study clarifies the antibacterial mechanism of FeS2 and offers a synergetic therapeutic platform with laser‐mediated Fe 2+ release for antibacterial applications. Abstract : Ultrasmall FeS2 nanoparticles‐decorated hollow carbon nanospheres (CNSs) simultaneously release ferrous ions and sulfur ions through dissolution and disproportionation. The released sulfur exhibits a protective effect on Fe 2+, ensuring the stable existence of Fe 2+ to cause the death of bacteria. With the assistance of NIR irradiation, the CNSs@FeS2 show high antibacterial efficacy of synergistic hyperthermia/Fe 2+ therapy.